Description of seven new species of Theraphosidae (Araneae, Theraphosinae; Ischnocolinae) from Ecuador, along with the identification of a new variation of type I urticating setae - Dupérre, Nadine; Tapia, Elicio (Zootaxa, 2025)
Seven Theraphosidae species are newly described from Ecuador: from the genus Pamphobeteus Pocock, 1901: Pamphobeteus contramina sp. nov. (male, female) and Pamphobeteus guacamayos sp. nov. (female); from the genus Thrixopelma Schmidt, 1994, Thrixopelma supay sp. nov. (female) and Thrixopelma michaeli sp. nov. (male); from the genus Hapalopus Ausserer, 1875, Hapalopus planetearth sp. nov. (female); and from the genus Holothele Karsch, 1879, Holothele incurva sp. nov. (male) and, Holothele tsala sp. nov. (female). Images of a male syntype of Pamphobeteus augusti (Simon, 1889) are included, along with a distribution map of all Pamphobeteus species found in Ecuador. The presence and distribution of urticating abdominal setae type I, III and IV are discussed, and a new variation of type I urticating setae is described.